PENGARUH METODE DRILL MENGGUNAKAN MODIFIKASI MEJA DAN ALAT PANTUL TERHADAP KETERAMPILAN FOREHAND TENIS MEJA PADA SISWA SMAN 1 TANJUNG MORAWA - Valentino Sinaga, Ridho Albert; Zahro Siregar, Amalia; Gultom, Agung; Fitri Sinaga, Dinul; Samsuddin Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the drill method on students’ forehand stroke skills in table tennis. The study used a quantitative approach with a one group pretest-posttest design involving 23 students. Data were collected through forehand skill tests before and after treatment. The treatment consisted of structured and repetitive drill exercises to improve accuracy and consistency. The results showed that the average pretest score of 5.04 increased to 7.61 in the posttest with an average gain of 2.57. The findings indicate that the drill method positively improved students’ forehand stroke skills in table tennis learning.